2018
DOI: 10.1186/s13104-018-3638-5
|View full text |Cite
|
Sign up to set email alerts
|

First molecular screening of Plasmodium species in ungulates from Southern Brazil

Abstract: ObjectiveDespite malaria epidemiology has been extensively studied in primates, few studies were conducted in ungulates. After half a century without descriptions of Plasmodium spp. in deer since its first identification, recent research has rediscovered Plasmodium on ungulates in Africa, Asia, North America and South America, including Central Brazil. Here, a captive herd was evaluated in southern Brazil using light microscopy and PCR. DNA samples were tested for fragment amplification of two Plasmodium spp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Spesies yang ditemukan dari kedua negara tersebut adalah P. bubalis [14,15]. Upaya pelacakan parasit Plasmodium spp pada binatang rusa dilakukan juga di sebuah kebun binatang di Brasil namun belum dapat mendeteksi keberadaannya pada seluruh populasi yang ada [16].…”
Section: Pendahuluanunclassified
“…Spesies yang ditemukan dari kedua negara tersebut adalah P. bubalis [14,15]. Upaya pelacakan parasit Plasmodium spp pada binatang rusa dilakukan juga di sebuah kebun binatang di Brasil namun belum dapat mendeteksi keberadaannya pada seluruh populasi yang ada [16].…”
Section: Pendahuluanunclassified
“…Until now, there have been very limited number of research studies in ungulate malaria parasites using molecular biology approach. Recently, studies led by Templeton et al (2016) and Kaewthamasorn et al (2018) confirmed the findings of malaria in water buffaloes and goats in Thailand and later followed by the two reports in pamper deer by Asada et al (2018) and dos Santos et al (2018) in Brazil.…”
Section: Introductionmentioning
confidence: 71%
“…Among 6 provinces, river buffaloes in Chachoengsao Province showed the highest prevalence of malaria infection, matching with the finding of Templeton et al, 2016. Although study of buffalo malaria was still limited, there were some research studies on other ungulates. Elsewhere, a study regarding ungulate malaria was conducted in Southern Brazil but no positive sample was found owing to the cervid blood samples were collected at only single time point so parasitemia level may fluctuate over the parasite's life cycle (dos Santos et al, 2018). Another study proved that there was a close relationship between Plasmodium sequences detected from South American pampas deer (Ozotoceros bezoarticus) to P. odocoilei clade 2 in North American whitetailed deer (Odocoileus virginianus) (Asada et al, 2018).…”
Section: Discussionmentioning
confidence: 99%